Home-based management of hypoxaemic COVID-19 patients: design of the Therapy@Home pilot study - Frans H Rutten; Lisette Schoonhoven; Josi A Boeijen; Roderick P Venekamp; Karin A H Kaasjager; Rick T van Uum; Dorien L M Zwart; Alma C van de Pol; Karin Smit; Robert van den Broek; Wilma Bijsterbosch (BMJ Open)
Introduction During the COVID-19 pandemic, hospital capacity was strained. Home-based care could relieve the hospital care system and improve patient well-being if safely organised.We designed an intervention embedded in a regional collaborative healthcare network for the home-based management of acutely ill COVID-19 patients requiring oxygen treatment. Here, we describe the design and pilot protocol for the evaluation of the feasibility of this complex intervention.Methods and analysis Following a participatory action research approach, the intervention was designed in four consecutive steps: (1) literature review and establishment of an expert panel; (2) concept design of essential intervention building blocks (acute medical care, acute nursing care, remote monitoring, equipment and technology, organisation and logistics); (3) safety assessments (prospective risk analysis and a simulation patient evaluation) and (4) description of the design of the pilot (feasibility) study aimed at including approximately 15–30 patients, sufficient for fine-tuning for a large-scale randomised intervention.Ethics and dissemination All patients will provide written, informed consent. The study was approved by the Medical Ethics Review Committee of the University Medical Center Utrecht, the Netherlands (protocol NL77421.041.21). The preparatory steps (1–4) needed to perform the pilot are executed and described in this paper. The findings of the pilot will be published in academic journals. If we consider the complex intervention feasible, we aim to continue with a large-scale randomised controlled study evaluating the clinical effectiveness, safety and implementation of the complex intervention.